Evaluating Contemporary Christian Music in Seventh-day Adventists Church. A Descriptive Study in Central Nyanza Conference, Kenya - Ondoo, Beatrice Atieno (JOOUST, 2022)
Music is one of God's great gifts to man and is one of the most important elements in a spiritual program. It is an avenue of communication with God, and "is one of the most effective means of impressing the heart with spiritual truth". Dealing as it does with matters of eternal consequence, it is essential that music's tremendous power be kept clearly in mind. The Research is evaluating Contemporary Christian Music in Seventh-day Adventists Church. A descriptive study in Central Nyanza Conference, Kenya. The statement problem was that, Contemporary Christian Music (CCM), the music that seemed to be in famous among some youths and adults in the Seventh-day Adventist Church have infiltrated nearly all churches with questionable beats, styles and rhythms. Those who have had the courage to raise concerns about this type of music and experience coming into the church are often labeled as “legalists” or worse, accused of driving away the youth, and shamed into silence. This has created tension between young SDA faithful and the elderly counterparts. The latter opine that CCM promotes a shallow, distorted gospel without putting into considerations the philosophy and guidelines of music that contributes to the Christian spiritual life. The following are the objectives of the study: the relationship between leadership style in worship and music, the challenge of forms beats, styles and rhythm of CCM on faith of adherents in SDA church and the contribution of music in a Christian’s spiritual life in SDA church. The study was anchored on the secularization theory whose proponent is Max Weber. The target population was 210 and both quantitative and qualitative methods were used to collect data from the field. Simple random sampling was used to sample the respondents and key informants identified by purposive sampling which included church pastor and 4 church elders. The sampling techniques/ selection table by (Krejcie and Morgan 1970) was used to establish a sample size of 136. Data was collected using questionnaires, interviews and focus group discussions. Data was then analyzed using descriptive statistics and computation of the empirical data done using statistical package for the social sciences (SPSS). Findings of study in this research found out that the modern Christian Church seems to be departing from the principles of the SDA church and this has greatly affected the growth and survival of church. The level of understanding anticipated from both church leaders and their followers is missing in most cases and this at times results into conflicts in the church affecting all departments including music and worship team. Further results found out that, many of the musical compositions of CCM unwittingly promote pride and carnality in the instrumental composition even while the lyrics explicitly point to praising God. Lastly although music was not necessarily one of the functions of the church listed in the New Testament, it can be used as a means to center the Christian’s mind and heart on God. The research therefore recommends that; Adventist worship should endeavor to accommodate all the cultures that form the world church. This should be done without violating any biblical principles and the writings of Ellen G. White. Such a worship experience will keep church members attending the worship services regularly and help them be more involved in church activities.
Keywords: Seventh-day Adventists Church